A escrita palimpsestica de João Anzanello Carrascoza: uma leitura em Conto para uma só voz - Mello, Ana Maria Carneiro de (2022)
This dissertation aims to demonstrate how the resources of inter and intratextuality are manifested in the work of João Anzanello Carrascoza, in particular, in Conto para uma só voz (2020), which constitutes the corpus of this study. The bibliographical research, qualitative in nature, with exploratory and descriptive purposes, is based on the hypothesis that, through these resources, the author presents a single voice, formed by the union of multiple voices. To reach the objective and pave the way that leads to the observation of inter and intratextuality in Conto para uma só voz, the investigation is organized into three chapters. In the first, a brief analysis of themes, styles and forms in the author's work is presented, in order to offer an overview of his production as a whole and its recurrent features, such as poetic prose, the fragmentation of discourse, the hybridity of genres, the flow of thought, the elaboration of metaphors, the graphic game with words, silence, the resources of metafiction and the recourse to memory. In the second chapter, the concept of intertextuality is discussed based on the theoretical conceptions of Mikhail Bakhtin, Julia Kristeva and Gérard Genette, a discussion that allows, in the third chapter, to undertake the reading of Conto para uma só voz. In the narrative, the inter and intratextual discourses that the corpus establishes not only with other literary works, but also with other artistic languages are highlighted and analyzed, as well as with Carrascoza's own work, offering the text as a mosaic, constructed not in pieces, but from different voices, which are skillfully orchestrated and unified through the voice of the carrascozian narrator. The analysis of these dialogues allows us to see that such a voice, which often revisits the classics, can be compared to the voice that echoes in them due to the mastery with which the poetic discourse is constructed